PEMBERDAYAAN HUKUM UNTUK MENGUBAH PERILAKU MASYARAKAT PETANI DALAM RANGKA PENINGKATAN SOSIAL EKONOMI MASYARAKAT PETANI - Retno Hendrati Purwaningrum (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
To solve of the ineffectiveness of integrated pest control regulation, the law empowerment is likely needed such as firming up the regulation and improving law awareness of the farmers by regulation extension.